2010
DOI: 10.1097/inf.0b013e3181d8562c
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attitudes About Influenza Immunization and School-Based Immunization for School-Aged Children

Abstract: School-based immunization programs can increase immunization coverage by targeting parents for whom time demands and inconvenience are barriers, demonstrating that immunization is a social norm, and addressing concerns about influenza vaccine benefit and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
74
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 22 publications
5
74
1
Order By: Relevance
“…We found that this information led to changes in the proportion of individuals who planned to get vaccinated, suggesting higher vaccine acceptance, especially among those who were previously uninformed about herd immunity. Allison et al conducted a cross-sectional survey about school-based immunization programs, and they found that if parents believed that influenza vaccination was a social norm, they were more likely to have their child immunized [25]. In this study, we have also demonstrated the value of informing individuals about local vaccination rates, even when vaccination rates are low.…”
Section: Discussionsupporting
confidence: 51%
“…We found that this information led to changes in the proportion of individuals who planned to get vaccinated, suggesting higher vaccine acceptance, especially among those who were previously uninformed about herd immunity. Allison et al conducted a cross-sectional survey about school-based immunization programs, and they found that if parents believed that influenza vaccination was a social norm, they were more likely to have their child immunized [25]. In this study, we have also demonstrated the value of informing individuals about local vaccination rates, even when vaccination rates are low.…”
Section: Discussionsupporting
confidence: 51%
“…Parents are aware of the concept of herd immunity, the idea that this diminished risk of contagion, in turn, will provide better protection to each child. The importance of decreased cost and increased convenience of school vaccination also were consistently noted as important across groups; these findings along with focus group concerns about parental desire to be with children for vaccination and concerns regarding competent vaccinators were also previously reported by Allison, et al 15 Also noted previously in the literature, 10 having the school have access to the vaccination record was viewed favorably by parents. Parental awareness and emphasis of the public health benefits of SLIPS and the importance these benefits play in their SLIP participation decision-making are unique findings not previously emphasized in the literature.…”
Section: Discussionsupporting
confidence: 53%
“…The largest reported barrier was parental concern their child would not want to receive vaccines at school without the parent present. This barrier was also reported in recent studies of parents of elementary-age students and adolescents [19,25,26]. To address this issue, it may be necessary for schools to allow parents to be present when their child is vaccinated at school.…”
Section: Discussionmentioning
confidence: 67%
“…A 2008 survey of parents of elementary school students reported 75% would consent for the influenza vaccine at school [19]. A study of parents of seventh grade students participating in a demonstration project for school-located delivery of the hepatitis B vaccine series demonstrated 76.6% of parents gave consent for their child to receive the vaccine at school [20].…”
Section: Discussionmentioning
confidence: 99%